Case Report: Upper extremity fibro-adipose vascular anomaly - Wang, Yutao; Pang, Xue; Yu, Sihai; Guo, Qingyong; Fan, Qichen; Song, Kuiquan; Sun, Yan (Frontiers in Surgery, 2025)
BackgroundFibro-Adipose Vascular Anomaly (FAVA) is a complex vascular malformation, usually presents as painful and slow-growing masses, and occurs commonly in the lower limb.MethodsThis paper describes a rare case of FAVA in the upper limb, which was successfully treated with surgery. A 26-year-old female was admitted with a painful mass in the left forearm. The MRI scan and Color Doppler ultrasound showed the mass located in the flexor carpi radialis of the left forearm.ResultsThe patient underwent resection of the involved muscle, and the histopathological examination confirmed the diagnosis of FAVA. She was followed up for 6 months after surgery without any relevant clinical event.ConclusionsSurgical management is an effective option for FAVA.